The Morphological Structures of the Topic of Patience in the Holy Qur’an and their Implications - Al-Shamry, Kadhim (Islamic Sciences Journal, 2023)
This research deals with the pure fluctuations of the substance (saber) patience in the holy quran and its implications, and the study is a semantic- morphological study. it also shows what happens to this article of pure fluctuations between the actual and the nominal, and the act came from it and its three sections: past, present and command. As for the nominal fluctuations, they came from: derived names such as the source, the name of the agent and the formulas of exaggeration, as well as the masculine and feminine, the singular, the dual and the plural.